Pemanfaatan Media Cetak dalam Pembelajaran IPS di Sekolah Dasar - Hadi Mustofa (Universitas Negeri Malang, 2016)
This study was designed to know the use of printed media in teaching Social Studies. It involved 15 teachers of 5th grade of elementary school and focused on their strategy on utilizing a printed media. The data were collected by interview, questionnaire, and observation, and were then analyzed statistically by percentages. The finding shows that the teachers utilize textbooks, newspaper, magazines, and pictures in their instructions. The process includes planning, implementation, and evaluation of media utilization